Personalization and consumer disclosure : considerations of ethics in digital marketing communications - Ahmad Wildan Fathoni (International Journal on Social Science, Economics and Art, 2024)
Personalization as a digital marketing communication strategy provides great benefits not only for marketers but also customers. Personalization strategies require efforts to collect and process various types of data from the consumers by marketers. Marketers as user and those who take advantage of technological developments in digital marketing have little concern about ethical and moral considerations in utilizing technology for the strategies used. On the other hand, it must be recognized that consumers themselves, as users and those who take advantage of technological developments in the digital marketing, don’t show behavior that prioritizes ethical considerations. This paper aims to make a theoretical review about ethical issues in personalization and consumer disclosure. This theoretical review was carried out through a literature study. Ethical consideration of personalization and consumer disclosure in marketing ethics will involve both positive ethics and normative ethics. The achievement of goals and benefits by both marketers and customers through various personalization strategies and consumer disclosure must be ethically justified. Normative ethics provide an acceptable rational basis for ethical justification, and positive ethics provide support for understanding empirically any ethically problematic decisions, actions and marketing strategies.